Improvement in the biological standard of living in 20th century Korea: Evidence from age at menarche. Issue 1 (9th June 2016) - Sohn, Kitae
Abstract : Objectives: We used age at menarche to understand improvement in the biological standard of living in South Korea during the 20th century. Methods: The main dataset, the Korean National Health and Nutrition Examination Survey, provided a consistent source of nationally representative data with a large number of observations over a long period of time. We calculated mean ages at menarche by birth year and estimated the rate of decrease in age at menarche, while avoiding survival bias. Results: The mean age at menarche decreased from 16.64 for the birth year 1941 to 12.68 for the birth year 1992, decreasing 0.78 (or 0.81 in a regression) years per decade for the period. Comparisons with other populations demonstrate that this is the fastest rate of decline ever known. In contrast to other developed countries, the decreasing rate in Korea does not appear to slow. We also compared the trend in age at menarche to that of height and found that the rate of increase in height is also the fastest in history. Conclusions: Age at menarche is an appropriate index of change in the general standard of living in South Korea over the 20th century. Am. J. Hum. Biol. 29:e22882, 2017. © 2016 Wiley Periodicals, Inc.